1983
DOI: 10.1042/bj2110323
|View full text |Cite
|
Sign up to set email alerts
|

Studies of the limited degradation of mucus glycoproteins. The effect of dilute hydrogen peroxide

Abstract: 1. The action of dilute H2O2 on a series of ovarian-cyst glycoproteins and glycopolypeptides was investigated. 2. Both native glycoproteins and the glycopolypeptides were carbohydrate-rich, of relatively low molecular weight and of simple structure. 3. At pH 5.6 and 37 degrees C, exposure to H2O2 for a limited time brought about a partial degradation, the molecular weight being decreased by 2-4-fold. 4. Carbohydrate analysis showed very little change in the oligosaccharide moiety, apart from a small decrease i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
37
0

Year Published

1984
1984
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(38 citation statements)
references
References 40 publications
1
37
0
Order By: Relevance
“…The sugar moieties in mucus may act similarly to mannitol and glucose in scavenging hydroxyl radical and H202 (45,46). Mucus glycoproteins react with H202; in the process both H202 and glycoproteins are degraded (44,47,48 (52), increased nonspecific airway reactivity, increased specific airway resistance, increased respiratory frequency on exercise, and an involuntary reduction of maximal inspiratory capacity (53). It should be noted that 03 decreases mucociliary transport in sheep (54) and other species in contrast to the human data mentioned above.…”
Section: Nonenzymatic Antioxidant Defensesmentioning
confidence: 48%
“…The sugar moieties in mucus may act similarly to mannitol and glucose in scavenging hydroxyl radical and H202 (45,46). Mucus glycoproteins react with H202; in the process both H202 and glycoproteins are degraded (44,47,48 (52), increased nonspecific airway reactivity, increased specific airway resistance, increased respiratory frequency on exercise, and an involuntary reduction of maximal inspiratory capacity (53). It should be noted that 03 decreases mucociliary transport in sheep (54) and other species in contrast to the human data mentioned above.…”
Section: Nonenzymatic Antioxidant Defensesmentioning
confidence: 48%
“…This proposal is based on the fact that certain sugars such as glucose or mannitol are potent hydroxyl radical scavengers, and mucus contains very high concentrations of some similar sugars (Nacetylglucosamine, galactose and fucose). Conversely, the mucus gel cover of the gastric mucosal surfaces was degraded to fragments, while viscosity and gel-forming properties were reduced after reaction with hydroxyl radicals and hydrogen peroxides [41,42]. It was reported that this fragmentation with a decrease in the viscosity of gastric mucus accompanied by an increase in its thiobarbituric acid reactivity is indicative of oxidative damage to the tissues [43].…”
Section: Discussionmentioning
confidence: 99%
“…H2O2 has been reported to severely fragment proteins such as myosin, but not lysozyme. Conversions of histidine into aspartic acid, as well as the loss of methionine, tyrosine, cysteine, and proline, may be involved in the cleavage of peptide bonds 33,34) . Statherin, which contains 62 residues, is rich in proline (7 residues) and methionine (3 residues) 35) and may be degraded into small fragments, as is myosin 33) .…”
Section: Discussionmentioning
confidence: 99%
“…Conversions of histidine into aspartic acid, as well as the loss of methionine, tyrosine, cysteine, and proline, may be involved in the cleavage of peptide bonds 33,34) . Statherin, which contains 62 residues, is rich in proline (7 residues) and methionine (3 residues) 35) and may be degraded into small fragments, as is myosin 33) . Indeed the in-office bleaching agent we used, whose active ingredient is a high concentration of H 2O2, was shown to be effective for bleaching 36) .…”
Section: Discussionmentioning
confidence: 99%